2022
DOI: 10.3389/fonc.2022.769203
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Folate Receptor-Positive Circulating Tumor Cells Are Associated With Occult Peritoneal Metastasis and Early Recurrence in Gastric Cancer Patients: A Prospective Cohort Study

Abstract: BackgroundThe aim of this study is to explore the clinical feasibility of detecting folate receptor-positive circulating tumor cells (FR+ CTCs) for predicting peritoneal metastasis and short-term outcome in gastric cancer patients.MethodsThis is a prospective, single-center, observational study. We applied ligand-targeted enzyme-linked polymerization method to detect preoperative FR+ CTC levels in peripheral blood. We evaluated the diagnostic value of FR+ CTCs and other biomarkers in predicting peritoneal meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…In all, 28 eligible studies 19 , 20 , 27 52 containing 2383 patients were enrolled for analysis ( Figure 1 ). Table 1 shows the basic characteristics and experimental design variables of all included studies.…”
Section: Resultsmentioning
confidence: 99%
“…In all, 28 eligible studies 19 , 20 , 27 52 containing 2383 patients were enrolled for analysis ( Figure 1 ). Table 1 shows the basic characteristics and experimental design variables of all included studies.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, FR + CTCs have been shown to serve as prognostic markers in several cancer types, including gastric, breast and lung cancers (38)(39)(40). In a prospective cohort study including 132 gastric cancer patients, combined model including FR + CTC level and other biomarkers (CA19-9, prealbumin and peripheral lymphocyte count) presented high sensitivity (100%) and moderate specificity (59.3%) in predicting peritoneal metastasis, the preoperative FR + CTC level could also predict short-term recurrence after surgery (38). In another prospective study to investigate the prognostic and predictive significance of FR + CTC in non-small cell lung cancer patients who underwent surgery, patients with lower preoperative CTC level had longer relapse-free FIGURE 2 survival (RFS) and OS, CTC level (HR = 4.10) and pathological stage (HR = 3.16) were independent prognostic factors of RFS (40).…”
Section: Discussionmentioning
confidence: 99%
“…As FRs are also highly expressed in PC, our previous study has shown that FR + CTCs have potential as a biomarker for the diagnosis of PC and LT-PCR is feasible and reliable for detecting FR + CTCs in patients with PC ( 32 ). In addition, FR + CTCs have been shown to serve as prognostic markers in several cancer types, including gastric, breast and lung cancers ( 38 40 ). In a prospective cohort study including 132 gastric cancer patients, combined model including FR + CTC level and other biomarkers (CA19-9, prealbumin and peripheral lymphocyte count) presented high sensitivity (100%) and moderate specificity (59.3%) in predicting peritoneal metastasis, the preoperative FR + CTC level could also predict short-term recurrence after surgery ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…This approach includes positive selection with antibodies against tumor-associated antigens such as EpCAM, CKs, mucin-1, human epidermal growth factor receptor 2, or epithelial growth factor receptor [50][51][52] and negative selection with antibodies against the common leukocyte antigen CD45 [53]. The CellSearch system (Veridex) is the most widely used antibody-based isolation technique and the only one approved by the Food and Drug Administration (FDA) for the detection of CTCs in the blood of some tumor patients [54][55][56], which has a greater benefit as a diagnostic and prognostic indicator for patients with metastatic disease [34,37]. However, imposing EpCAM bias on the enriched CTCs population is an obvious drawback of immunocapture methods, including CellSearch [57].…”
Section: Detection Methods Of Ctcsmentioning
confidence: 99%
“…In this study, the authors also found that the number of CTCs in stage III GC patients was higher than that in stage I GC patients and that the overall survival rate of patients with more than 5 CTCs was lower. Dan Zeng et al [ 37 ] used ligand‐targeted polymerase chain reaction to detect the levels of folate receptor-positive CTCs in blood samples from GC patients and found that preoperative CTCs levels have a diagnostic value in predicting peritoneal metastases in GC. Furthermore, Huang et al [ 30 ] found CTCs in 10.8% of the resected group with a high recurrence rate and 60.2% of the unresectable group, but not in the healthy control group.…”
Section: Clinical Application Of Liquid Biopsy Biomarkers In Gcmentioning
confidence: 99%